NATIONAL CHARACTER BUILDING THROUGH KI HAJAR DEWANTARA'S HUMANISTIC EDUCATION IN RESPONDING TO STEREOTYPES OF INDONESIAN PEOPLE - Fitriyani, Anindyta; Parhan, Muhamad (Journal Civics And Social Studies, 2024)
Education fundamentally revolves around behavior, and a nation anticipates its citizens to exhibit behavior that aligns with the nation's esteemed values. This study seeks to examine six attributes of Indonesians in the 21st century and evaluate Ki Hajar Dewantara's humanistic philosophy as a potential means of cultivating a humanistic society in Indonesia as a national character-building strategy. This study employs library research methods. The employed data analysis approaches include reduction, presentation, and conclusion. The research findings indicate that the six attributes of Indonesians, as identified by Mochtar Lubis, namely hypocrisy, aversion to accountability, feudalistic conduct, superstition, artistic inclination, and fragility, continue to be observable in contemporary times. Ki Hajar Dewantara's humanist philosophy, implemented at the Taman Siswa school, offers a philosophical framework that can address Mochtar Lubis' six characteristics of Indonesian in the 21st century. This can be achieved through the principles of tetep, antep, mantep; ngandel, kandel, bandel; ngerti, ngroso, nglakoni; Ing Madya Mangun Karsa; as well as Ki Hajar Dewantara's views on education as a means of emancipating individuals both physically and mentally.